2005
DOI: 10.1111/j.1742-4658.2005.05077.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aryl acid adenylation domains involved in bacterial siderophore synthesis

Abstract: Aryl acid adenylation domains are the initial enzymes for aryl‐capping of catecholic siderophores in a plethora of microorganisms. In order to overcome the problem of iron acquisition in host organisms, siderophore biosynthesis is decisive for virulence development in numerous important human and animal pathogens. Recently, it was shown that growth of Mycobacterium tuberculosis and Yersinia pestis can be inhibited in an iron‐dependent manner using the arylic acyl adenylate analogue 5′‐O‐[N‐(salicyl)‐sulfamoyl]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 29 publications
(37 reference statements)
1
108
0
1
Order By: Relevance
“…The in vitro and in-culture inhibition efficacy of SAL-AMS was confirmed in further studies (215,303,304,324). Due to the in vitro IC 50 values, which were in the range of the enzyme concentrations used, and the observed noncompetitive inhibition of the analogue with respect to salicylate, SAL-AMS was suggested to be a tight binding inhibitor (91 zyme inhibition were made during further studies with the same compound and several derivatives thereof; however, the compounds were always found to be fully competitive for both ATP and the corresponding aryl acid (44,215,304). Further sulfamate-linked analogues have been derivatized mainly in their aryl and glycosyl domains (Fig.…”
Section: Siderophore Pathway Inhibitorsmentioning
confidence: 68%
“…The in vitro and in-culture inhibition efficacy of SAL-AMS was confirmed in further studies (215,303,304,324). Due to the in vitro IC 50 values, which were in the range of the enzyme concentrations used, and the observed noncompetitive inhibition of the analogue with respect to salicylate, SAL-AMS was suggested to be a tight binding inhibitor (91 zyme inhibition were made during further studies with the same compound and several derivatives thereof; however, the compounds were always found to be fully competitive for both ATP and the corresponding aryl acid (44,215,304). Further sulfamate-linked analogues have been derivatized mainly in their aryl and glycosyl domains (Fig.…”
Section: Siderophore Pathway Inhibitorsmentioning
confidence: 68%
“…Siderophore synthesis has recently been identified as a target for antibiotic development (12,37,38). In these studies, the NRPS adenylation domain has served as the target for inhibitor design.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][63][64][65] In this report we have systematically investigated the SAR of the glycosyl domain of our salicyl-nucleoside bisubstrate inhibitor. In particular, in vitro results against MbtA showed that deletion of the 2′, 3′, and 4′ oxygen atoms were generally well tolerated, while modifications making the sugar more (13) or less (11) flexible were detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…The homology model and docking runs were configured as described 43 , except that water molecules were held fixed during the conformational search. 10,000 search steps were performed for each compound.…”
Section: Docking Studiesmentioning
confidence: 99%